ANALISIS USABILITY SISTEM DELIMA MENGGUNAKAN METODE SYSTEM USABILITY SCALE DAN USER EXPERIENCE QEUESTIONNAIRE - sherliana, sherliana; Sulistyorini, Prastuti; Wibowo, Ari (Bapelitbang Kabupaten Batang, 2025)
The DELIMA website is a digital service provided by the Batang Regency Government that is used to apply for research and internship permits online. This service was developed to support digital transformation and improve the efficiency of public services. This study aims to analyze the usability and user experience (UX) of the DELIMA website using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) methods. A total of 19 respondents who have used this website participated in the study. The SUS test results showed an average score of 82.10, which is classified as Excellent with a grade of B, indicating a good level of user acceptance. Meanwhile, the UEQ results showed a positive user experience, with the aspects of Attractiveness (1.85), Efficiency (1.99), and Accuracy (1.86) falling into the Excellent category, while Clarity (1.95), Stimulation (1.66), and Novelty (1.38) fell into the Good category. These results show that the DELIMA website has fulfilled the functional and emotional aspects of users well, although the aspects of novelty and stimulation still need to be improved.